Efficacy of serum procalcitonin to predict spontaneous preterm birth in women with threatened preterm labour: a prospective observational study - Guillaume Ducarme; François Desroys du Roure; Aurélie Le Thuaut; Joséphine Grange; Mathilde Vital; Jérôme Dimet (BMC, 2018)
Abstract Background A hypothesis of preterm parturition is that the pathogenesis of spontaneous preterm birth (sPTB) may be associated with an inflammatory process. Based on this theory, we have hypothesized that an inflammatory biomarker, procalcitonin (PCT), may be a good predictive marker of sPTB at the admission for threatened preterm labour (TPL). The present study was aimed to investigate the association between serum PCT and sPTB in women with TPL and to evaluate whether PCT levels may predict sPTB in women with TPL within 7 or 14 days. Methods In a prospective observational laboratory-based study, women with singleton pregnancies, TPL between 24 and 36 weeks and intact membranes, were enrolled between January 2014 and June 2016. Participants received routine medical management of TPL (tocolysis with atosiban, antenatal corticosteroids, and biological tests at admission (C-reactive protein, white blood cell count, and PCT measured on electrochemiluminescence immunoassay)). The primary endpoint was sPTB before 37 weeks of gestation. The value of serum PCT levels to predict sPTB within 7 or 14 days were evaluated using receiver-operating curves (ROC) analysis. Results A total of 124 women were included in our study. PCT levels did not statistically differ between women with sPTB (n = 30, 24.2%) and controls (n = 94) (median in ng/mL [interquartile range]: 0.043 [0.02-0.07] compared to 0.042 [0.02-0.13], respectively; P = 0.56). PCT levels did not also statistically differ between women with sPTB within 7 days (n = 7, 5.6%) or 14 days (n = 12, 9.7%) after testing and controls. Moreover, subgroup analysis revealed no difference among PCT levels at admission between 24 and 28 weeks, between 28 and 32 weeks and over 32 weeks, and controls. On the basis of the receiver-operating characteristic curve, the highest sensitivity and specificity corresponded to a PCT concentration of 0.038 ng/mL, with poor predictive values for sPTB within 7 or 14 days. Conclusion Serum PCT was not relevant to predict sPTB within 7 or 14 days in women admitted with TPL between 24 and 36 weeks, and thus it is not a suitable biological marker to confirm the hypothesis of an inflammatory process associated with preterm parturition. Trial registration Clinicaltrials.gov (NCT01977079), Registered 24 October 2013.